2002
DOI: 10.1523/jneurosci.22-03-00644.2002
|View full text |Cite
|
Sign up to set email alerts
|

Specific Gap Junctions Enhance the Neuronal Vulnerability to Brain Traumatic Injury

Abstract: Traumatic brain injury results in neuronal loss and associated neurological deficits. Although most research on the factors leading to trauma-induced damage focuses on synaptic or ionic mechanisms, the possible role of direct intercellular communication via gap junctions has remained unexplored. Gap junctions connect directly the cytoplasms of coupled cells; hence, they offer a way to propagate stress signals from cell to cell. We investigated the contribution of gap junctional communication (GJC) to cell deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
156
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(165 citation statements)
references
References 62 publications
7
156
1
1
Order By: Relevance
“…Lately, however, it has been suggested that sense controls do not provide any additional advantage over nonsense ODNs, especially because any potentially critical sequence motifs (recurring sequences of 3-8 bases in the mRNA) that may contribute to the structure or function of the targeted mRNA are lost (Stein, 1999). In addition, sense ODNs are known to produce nonspecific effects (Helene and Toulme, 1990;Nicot and Pfaff, 1997;Kalra and Kalra, 2000), including inhibition of the targeted protein (Georgieva et al, 1995), and therefore, several recent studies (in vivo and in vitro) have not used the sense control (Turchi and Sarter, 2001;Clayton et al, 2002;Frantseva et al, 2002;Grimpe et al, 2002;Torner et al, 2002). There also appears to be agreement that demonstration of antisense-induced suppression of the desired protein without any neurotoxicity and reversal of the behavioral changes after termination of antisense administration are essential to ascertain the efficacy and specificity of antisense (Nicot and Pfaff, 1997;Stein, 1999Stein, , 2001).…”
Section: Methodological Issues With Antisense Usementioning
confidence: 99%
“…Lately, however, it has been suggested that sense controls do not provide any additional advantage over nonsense ODNs, especially because any potentially critical sequence motifs (recurring sequences of 3-8 bases in the mRNA) that may contribute to the structure or function of the targeted mRNA are lost (Stein, 1999). In addition, sense ODNs are known to produce nonspecific effects (Helene and Toulme, 1990;Nicot and Pfaff, 1997;Kalra and Kalra, 2000), including inhibition of the targeted protein (Georgieva et al, 1995), and therefore, several recent studies (in vivo and in vitro) have not used the sense control (Turchi and Sarter, 2001;Clayton et al, 2002;Frantseva et al, 2002;Grimpe et al, 2002;Torner et al, 2002). There also appears to be agreement that demonstration of antisense-induced suppression of the desired protein without any neurotoxicity and reversal of the behavioral changes after termination of antisense administration are essential to ascertain the efficacy and specificity of antisense (Nicot and Pfaff, 1997;Stein, 1999Stein, , 2001).…”
Section: Methodological Issues With Antisense Usementioning
confidence: 99%
“…Alternatively, spread of sodium or calcium ions could instantly involve large number of neurons, resulting in more uniform damage (Frantseva et al, 2002). Here no evidence was obtained for spatial/ Figure 4 Role of the spinal cord and exogenous ATP in extending radiation injury to the unexposed brain.…”
Section: Vehicle Vehiclementioning
confidence: 99%
“…In this study, we attempted to explore whether specific gap-junction blockers affect the cellular sensitivity to ischemic injury in rats and whether such blockade diminishes the diffusion of reactive oxygen species (ROS) in vitro. Carbenoxolone (CBX) is effective in blocking gap-junction coupling [15] , interferes little with synaptic function in vivo and in vitro [16][17][18][19] , and induces minimal changes in intrinsic neuronal characteristics [20,21] .…”
Section: Introductionmentioning
confidence: 99%